Speciation of Potentially Toxic Metals from the Mine Impacted soils: A Case Study of Riruwai Mining Area, Kano State, Northern Nigeria - Badamasi, Hamza; Hassan, Umar Faruk; Adamu, Harami Malgwi; Baba, Nasirudeen Mohammed; Adamu, Dahiru Ajiya; Baba, Haruna (Department of Chemistry Faculty of Science and Technology Walisongo, 2023)
Mining and smelting sectors contribute significantly to global growth on a regional and local scale. However, the operations are causing significant environmental damage, particularly pollution of the soil with potentially toxic metals (PTMs). In this study, the speciation of PTMs (arsenic, cadmium, chromium, mercury, manganese, nickel, lead and zinc) from the mine impacted soils of Riruwai mining area was investigated using a modified Tessier sequential extraction method. The findings of the study revealed that all the PTMs examined are considerably associated with non-residual fractions in all the sampling locations. This indicates that all the PTMs investigated in the study area may be highly mobile in the soils and hence potentially toxic. The concentrations of PTMs in the soil’s geochemical fractions were found to vary with the sampling locations, with active mining sites significantly (p ≤ 0.05) recording the highest value, followed by farmland, while the lowest value was reported at the control site. Therefore, to protect the environment and the health of the local populace, PTMs in the soils of the study area should be regularly monitored and a treatment program should be put in place.